The Idea of Tarikh in Syamarih fi Ilmi Tarikh by Jalal al-Din al-Suyuti - A. Nurkiman, E. Roni; Rohmatillah, Tolib; Permana, Agus (Historia Madania: Jurnal Ilmu Sejarah, 2024)
This study delves into "Syamarih fi ilmi Tarikh" by Jalaluddin al-Sayuti, an exploratory work on historical methodologies. The objective is to illuminate the essence of historical study through al-Sayuti’s lens, highlighting the importance of understanding history as a discipline. Despite its profound contributions to historical discourse, al-Sayuti’s text remains underexplored among scholars, signaling a gap in academic discussions on historical conceptualizations. Utilizing content analysis, this research uncovers al-Sayuti’s motives and his unique approach to presenting history. Our findings indicate that al-Sayuti perceives ’tarikh’ (history) as inherently linked to temporal dynamics, incorporating aspects of chronological, cyclical, and natural times. This conceptualization is closely tied to Islamic principles, suggesting that his interpretation serves not only as an academic endeavor but also as a reflection of Islamic civilization’s understanding of time. Al-Sayuti’s work, thus, provides insightful perspectives on the interplay between time and history, emphasizing the significance of temporal frameworks in shaping historical narratives. The conclusion underscores al-Sayuti’s contribution to historical thought, offering a nuanced view that enriches our comprehension of history as both a subject and a methodology. This research affirms the critical need to further investigate such foundational texts to enhance our grasp of historical sciences.